Prey depletion, interspecific competition, and the energetics of hunting in endangered African wild dogs, Lycaon pictus - Scott Creel; James Redcliffe; Ben Goodheart; Johnathan Reyes de Merkle; Henry Mwape; Stephanie Matsushima; Chase Dart; Kachama Banda; Bridget Mayani; Johane Njobvu; Reuben Kabungo; Michelo Mungolo; et al. (Proceedings of the National Academy of Sciences, 2025)
Large herbivores are in decline in much of the world, including sub-Saharan Africa, and true apex carnivores like the lion ( Panthera leo ) decline in parallel with their prey. As a consequence, competitively subordinate carnivores like the African wild dog ( Lycaon pictus ) are simultaneously experiencing a costly reduction in resources and a beneficial reduction in dominant competitors. The net effect is not intuitively obvious, but wild dogs’ density, survival, and reproduction are all low in areas that are strongly affected by prey depletion. To assess whether these correlations are causal, we tested the hypothesized mechanism, using data from 13 wild dog packs in two ecosystems to relate the energetic costs and benefits of hunting to variation in prey density, while controlling for the effects of local lion density, pack size, the number of dependent pups, and the level of protection. All of these variables affected the energetic costs and benefits of hunting. In areas with low prey density, the magnitude of movements and vectorial dynamic body acceleration (a measure of energy expenditure) both increased, the mass of killed prey decreased, and the number of kills per day did not change detectably. Programs to reduce or reverse the decline of large herbivore populations should be an effective means of improving the status of endangered subordinate competitors like the wild dog, and should be a high priority. Our results demonstrate the utility of research that integrates data from biomonitoring with direct, long-term observation of endangered species, their competitors, and their resources.